Manajemen Dakwah Perlindungan Anak dan Perempuan Fatayat NU: Studi atas Fatwa MUI dan Implikasinya bagi Pendidikan Islam - Siti Nuri Nurhaidah; Siti Rohanah (PT Rizkarya Cendekia Pustaka, 2025)
This article discusses the management of da'wah in the context of child and women's protection, emphasizing the fatwas of the Indonesian Ulema Council (MUI) and their implications for Islamic education. The phenomena of violence, exploitation, and discrimination against children and women continue to pose serious challenges in Indonesian society, both in domestic and public spheres. MUI, as a religious authority, has issued a number of fatwas related to the protection of children, women, pornography, narcotics, and sexual violence, which align with the maqāṣid al-sharī‘ah, particularly hifz al-nafs (protection of life) and hifz al-nasl (protection of lineage). This research employs a qualitative approach with document analysis of MUI's fatwas and relevant academic literature. The results indicate that MUI's fatwas can serve as a basis for da'wah management that is educational, transformative, and preventive, especially in the realm of Islamic education. The integration of fatwas into educational curricula. Gender-sensitive learning and strengthening family preaching are strategic steps to realize a generation that is moral, empowered, and protected. This article emphasizes the importance of synergy between MUI, Islamic educational institutions, the government, and society in carrying out child and women's protection preaching comprehensively.